PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN YAYASAN NDHOLO KUSUMO DI KABUPATEN PATI - Shodik, Ahmad; Budiyono, Rokhmad; Novandalina, Arini (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Productivity is a comparison between output (results) and input. If productivity increases, efficiency (time-material-labor) and work systems, production techniques and the skills of the workforce will increase. The aim of this research is to determine and analyze the mediating role of job satisfaction on the influence of compensation and work motivation on the work productivity of Ndholo Kusumo foundation employees in Pati Regency. The population in this study was 85 employees of the Ndholo Kusumo Foundation in Pati Regency. The sample in this study used the census method, where all members of the population were used as samples. This research variable uses independent variables consisting of compensation and work motivation, then work productivity as the dependent variable and the intervening variable is job satisfaction which mediates compensation and work motivation on employee work productivity. The data collection method uses a questionnaire. The data analysis method uses path analysis The Ndholo Kusumo foundation should include its employees in the BPJS Old Age Security and Pension Guarantee program, and the BPJS health program, then the foundation should implement a rolling system / rotation of job desks and the foundation reduce the workload on its employees or increase the time for completing work.